Income and consumption inequality in the Philippines: A stochastic dominance analysis of household unit records - Maria Rebecca J. Valenzuela; Wing-keung Wong; Zhu Zhen Zhen (Asian Development Bank Institute (ADBI), 2017)
In this paper, we employ stochastic dominance (SD) analysis on household unit records to measure relative welfare levels and investigate sources of inequality in the Philippines from 2000 to 2012. Using SD techniques developed in Chow, Valenzuela, and Wong (2016), we test for richness and poorness in the population across various social, economic, and demographic dimensions. Our SD composition approach and application of tests showed higher and improved relative welfare levels exist for urban, non-agricultural households, and that compared with wages and business income, other sources of income have grown in importance in narrowing welfare gaps over time. We also found that gender of household head and education attainments matter for welfare outcomes. In terms of age, we found high concentrations of poor income units among the youngest cohort (aged 30 and under), and high concentrations of richer income units in the older, over-60 cohort. These results help explain persistently high levels of income inequality observed in the Philippine economy.
Keywords: I32; J11; J14; 330; Economics; Gender; Poverty; Philippines